Evidence for density-dependent e ects on body composition of grizzly bears in the Greater Yellowstone ecosystem - Corradini, A.; Haroldson, M. A.; Cagnacci, F.; Costello, C. M.; Bjornlie, D. D.; Thompson, D. J.; Nicholson, J. N.; Gunther, K. A.; Wilmot, K. R.; van Manen, F. T. (Associazione Teriologica Italiana, 2022)
In large mammals, individual performance and local population density are intrinsically linked through a feedback mechanism that leads to demographic changes. Density-independent factors, such as resource availability or landscape changes, also influence this feedback process by lowering carrying capacity and increasing density dependence. Although studying the link between individual performance, population density, and environment in long-lived species is crucial for understanding ecological processes in today's fast-changing world, the availability of long-term data often limits the capacity to research such mechanisms in free-roaming animals. In this study, we tested whether density-dependent factors influenced changes in grizzly bear (Ursus arctos) lean body mass and fat percentage, both measures of individual performance, during years of environmental changes in the Greater Yellowstone Ecosystem. For this purpose, we used longitudinal morphometric data from over 400 grizzly bears captured for research purposes between 2000 and 2020. We used lean body mass measurements of individual grizzly bears to fit population-level, sex-specific growth curves, and fat percentage to estimate body fat accumulation over the active season (May to October). Thus, we tested the effect of local population density on growth and fat levels, as determined by a spatio-temporally index based on grizzly bear telemetry data, while controlling for ecosystem variability and human-caused disturbance. Individual lean body mass was negatively related to population density, especially among young females, indicating a performance-density relationship across life-stages and sex. In contrast, despite significant landscape-level changes over the last two decades, our findings revealed that grizzly bear body fat levels and rate of accumulation were unaffected by population density. This suggested that sufficient food resources were available on the landscape to accommodate successful, plastic shifts in feeding tactics in the face of ...